Length-weight Relationship and Condition Factors of Endemic Fish, Lagusia micracanthus Bleeker, 1860 (Pisces: Terapontidae) in Gilireng River, Wajo Regency, Indonesia - Neneng Rahayu Ningsih; Sharifuddin Bin Andy Omar; Abdul Haris; Muhammad Nur; Rakhma Fitria Larasati (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Research on pirik endemic fish (Lagusia micracanthus) was first conducted in the Gilireng River. Based on the length-weight relationship, the growth type of pirik fish in the Gilireng River is isometric. The average size distribution, total length, and body weight of female fish were greater than those of male fish though not statistically significant. The Gilireng River water conditions are sufficient to support the growth of endemic pirik fish. Abstract Lagusia micracanthus or locally known as pirik fish and is the only endemic freshwater fish from the family Terapontidae. To date, published information related to biological aspects of this species in the Gilireng River, Arajang Village, Wajo Regency, is unavailable. This study aims to determine the lengthâˆ’weight relationship and condition factors of L. micracanthus fish populations in the Gilireng River. Fish sampling was performed once a month January 2022 to June 2022.The fish collected from Gilireng River comprised 69 male and 66 females during the study period. Pirik (L. micracanthus) in the Gilireng River demonstrated nearly an isometric growth pattern. Condition factor values ranged from 0.6455 to 4.3239, and the average condition factor values for female fish were smaller than male fish. The result of this study has contributed to the knowledge of the endemic pirik fish population in the Gilireng River that could assist fishery management scientists in conducting studies on the management of these fish.